2008
DOI: 10.1038/sj.clpt.6100459
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Characterization of Sulfasalazine Disposition Based on NAT2 and ABCG2 (BCRP) Gene Polymorphisms in Humans

Abstract: The role of breast cancer resistance protein (BCRP), an efflux ABC transporter, in the pharmacokinetics of substrate drugs in humans is unknown. We investigated the impact of genetic polymorphisms of ABCG2 (421C>A) and NAT2 on the pharmacokinetics of sulfasalazine (SASP), a dual substrate, in 37 healthy volunteers, taking 2,000 mg of conventional SASP tablets. In ABCG2, SASP AUC(0-48) of C/C, C/A, and A/A subjects was 171 +/- 85, 330 +/- 194, and 592 +/- 275 microg h/ml, respectively, with significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
118
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 41 publications
(109 reference statements)
8
118
1
Order By: Relevance
“…The study in question by Adkison et al (2010) used oral sulfasalazine enteric-coated tablets and, in fact, surprisingly showed no significant pharmacokinetic changes with oral coadministration of the BCRP inhibitor, pantoprazole, or a significant genedose effect of the BCRP 421 C.A functional polymorphism. These results stand in stark contrast to three independent clinical studies using oral immediate-release sulfasalazine tablets and/or suspension formulation, where significant 2-to 4-fold increases in sulfasalazine exposure were observed in carriers of the BCRP 421 C.A polymorphism and during coadministration of an oral BCRP inhibitor (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012), as well as three independent preclinical studies in Bcrp-knockout mice and rats (Zaher et al, 2006;Shukla et al, 2009;Zamek-Gliszczynski et al, 2012). As discussed by Adkison et al (2010), an accidental flaw in the execution of their study demonstrated the importance of proper formulation selection (suspension or immediate release, but not extended release), rather than disproving the utility of sulfasalazine as a marker of BCRP activity in humans.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…The study in question by Adkison et al (2010) used oral sulfasalazine enteric-coated tablets and, in fact, surprisingly showed no significant pharmacokinetic changes with oral coadministration of the BCRP inhibitor, pantoprazole, or a significant genedose effect of the BCRP 421 C.A functional polymorphism. These results stand in stark contrast to three independent clinical studies using oral immediate-release sulfasalazine tablets and/or suspension formulation, where significant 2-to 4-fold increases in sulfasalazine exposure were observed in carriers of the BCRP 421 C.A polymorphism and during coadministration of an oral BCRP inhibitor (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012), as well as three independent preclinical studies in Bcrp-knockout mice and rats (Zaher et al, 2006;Shukla et al, 2009;Zamek-Gliszczynski et al, 2012). As discussed by Adkison et al (2010), an accidental flaw in the execution of their study demonstrated the importance of proper formulation selection (suspension or immediate release, but not extended release), rather than disproving the utility of sulfasalazine as a marker of BCRP activity in humans.…”
contrasting
confidence: 99%
“…However, we noticed that the authors have missed some critically important concepts when referring to drugs that have complex permeability/efflux and atypical metabolism, whose disposition has been mechanistically uncovered by reverse translation (working from bedside back to the bench). These omissions resulted in the description of sulfasalazine as a poor BCRP substrate in humans, even though it is currently one of the two best available clinical BCRP probes along with rosuvastatin (Urquhart et al, 2008;Yamasaki et al, 2008;Kusuhara et al, 2012).The authors selectively used one specific clinical study as "proof" that "sulfasalazine PK was not affected in individuals with impaired BCRP function, nor when coadministered with [a BCRP inhibitor]" (Poirier et al, 2014). The study in question by Adkison et al (2010) used oral sulfasalazine enteric-coated tablets and, in fact, surprisingly showed no significant pharmacokinetic changes with oral coadministration of the BCRP inhibitor, pantoprazole, or a significant genedose effect of the BCRP 421 C.A functional polymorphism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulative in vivo studies, particularly involving Bcrp knockout (Bcrp -/-) mice, have demonstrated the important role BCRP plays in drug disposition, limiting oral absorption and penetration into the brain and testis (8), and mediating biliary and urinary excretion of xenobiotics such as pitavastatin and methotrexate (1, [9][10][11]. Pharmacogenomic studies focusing on a single nucleotide polymorphism frequently observed in Asians (421C.A) elucidated the importance of BCRP in systemic exposure to orally administered sulfasalazine and rosuvastatin (12,13). Because of the lack of a suitable probe, the role of BCRP in the elimination of BCRP substrates from the systemic circulation and their distribution in the brain has not been investigated.…”
mentioning
confidence: 99%